Interprofessional, student-led intervention to improve insulin prescribing to patients in an Acute Surgical Receiving Unit. Issue 2 (29th June 2018) - Tully, Vicki; Al-Salti, Suaad; Arnold, Amy; Botros, Shady; Campbell, Iona; Fane, Rachel; Rowe, Iain; Strath, Alison; Davey, Peter
Abstract : Our aim was to test the feasibility of interprofessional, workplace-based learning about improvement through a 4-week placement for one medical and two pharmacy final year students in an Acute Surgical Receiving Unit (ASRU). The target was insulin because this is a common, high-risk medicine in this ASRU and the intervention was medicines reconciliation. Baseline data were collected from 10 patients and used to construct a cause and effect diagram and a process map through feedback and discussions with staff. Hypoglycaemia occurred in four patients but hyperglycaemia occurred in eight patients, of whom six were placed on intravenous insulin infusion (IVII). We estimated that £2454 could be saved by preventing one patient from going on IVII. The students designed and tested a sticker to improve medicines reconciliation for insulin patients. An online form was created to capture clinician feedback on the layout and usability of the sticker. The intervention was associated with improvements in the reliability of medicines reconciliation. The students' work contributed to a larger project to reduce the risk of hypoglycaemia in the ASRU. This proved beneficial in enabling the students to engage with the clinical team. Nonetheless, it was challenging for students from two Universities to get a shared understanding of improvement methods and work effectively with the clinical team. The students said that they learnt more about quality improvement in a working healthcare environment than they would ever learn in a classroom and they valued the opportunity to work with students from other healthcare backgrounds in practice. Despite the additional staff time required to support students from two Universities, both have supported continuation of this work.